Analisis Hubungan Pertumbuhan Ekonomi Dengan Kemiskinan dan Belanja Modal Pemerintah Daerah, Penyerapan Tenaga Kerja, dan Indeks Pembangunan Manusia - Hardana, Ali; Nasution, Jafar; Damisa, Arti; Lestari, Sry; Zein, Aliman Syahuri (Jurnal Studi Pemerintahan dan Akuntabilitas, 2023)
Purpose: The aims of this study are to examine the effect of capital expenditures of local governments, labor absorption and the Human Development Index on economic growth and poverty in 35 districts/cities in Central North Sumatra. Methodology/approach: This research uses research quantitative. while the data sources used by researchers are secondary data. There are variable capital expenditures of local governments, labor absorption, and the Human Development Index as an exogenous variable, while economic growth and poverty level as an endogenous variable. This study uses panel data which combines time series data and cross-section. These data were analyzed using Structural Equation Modeling with AMOS 20 program. Results/findings: The results showed that the four proposed hypotheses are accepted and the hypothesis is rejected. Hypothesis 1 suggests that the local government capital expenditure significantly positive effect on economic growth. Hypothesis 2 suggests that labor absorption significantly positive effect on economic growth. Hypothesis 3 suggests that the Human Development Index significantly positive effect on economic growth. Hypothesis 4 suggests that economic growth has no significant effect on poverty. Hypothesis 5 suggests that the Human Development Index is a significantly negative effect on poverty Limitation: Multivariate normality testing was carried out by looking at the multivariate CR value with results of ±2.58.